TRANSFORMASI LAYANAN PUBLIK MELALUI STANDAR PELAYANAN DI KANTOR KELURAHAN PA’BAENG-BAENG - Akil, Adha; Tonapa, Jessica Fransisca (Politeknik STIA LAN Makassar, 2024)
Pa'baeng-Baeng Subdistrict Office located in Makassar City, still needs to prepare and establish a service standard document as a benchmark in providing services to the Community. The absence of service standards indirectly indicates that the Pa'baeng-Baeng Subdistrict Office needs guidelines or references to provide public services. This research aims to show that the Pa'baeng-Baeng Subdistrict Office has indicators in providing services and increasing community satisfaction as service recipients. The research method used in this research is descriptive qualitative with data collection methods, namely interviews with the Village Head, staff and community recipients of services, observations regarding the services provided and document review. Focused Group Discussion (FGD) was conducted with the Village Office officials and the Community to obtain input in the design of Service Standards. The results of this research are 5 (five) types of service standards and service announcements that the village head has determined. The existence of service standards is hoped to become a basis for providing services to the community satisfaction, ensuring accountability and increasing community satisfaction with services at Pa'Baeng-Baeng Subdistrict Office.